Educational event as a component of the system of language training of foreign students - Kravchenko, Yu. V.; Gnatenko, S. A.; Tkachenko, V. Yu.; Кравченко, Юлія Володимирівна; Гнатенко, Світлана Анатоліївна; Ткаченко, Валерія Юріївна (My University, 2024)
The article discusses one of the aspects of the educational process organized by the Department of Language Training at Zaporizhzhia State Medical and Pharmaceutical University, which faces certain challenges due to psychophysiological and linguistic factors. The former are related to overcoming differences in the sphere of education, requirements and control systems, as well as mastering new social-cultural, educational spaces, and moral-ethical norms of behavior; the latter are due to the complete absence or insufficiency of language training. All these and other problematic issues are in the focus of the tutor during the educational process. These two types of activities are interconnected, as the educational process is aimed at acquiring knowledge, professional skills and abilities, while the upbringing process contributes to the personal improvement of the student. Extracurricular educational activities allow students to improve their knowledge of the Ukrainian language, develop communicative abilities, reveal their inner potential and feel the team spirit. This, in turn, improves the quality of two-way communication between teacher → student and student → teacher.
Keywords: educational process; extracurricular work; psychophysiological factor; speech factor; Ukrainization